The impact of age on load-related dorsolateral prefrontal cortex activation - Toepper, Max; Gebhardt, Helge; Bauer, Eva; Haberkamp, Anke; Beblo, Thomas; Gallhofer, Bernd; Driessen, Martin; Sammer, Gebhard (Frontiers in Aging Neuroscience, 2014)
Healthy aging is accompanied by working memory-related functional cerebral changes. Depending on performance accuracy and the level of working memory demands, older adults show task-related patterns of either increased or decreased activation compared to younger adults. Controversies remain concerning the interpretation of these changes and whether they already manifest in earlier decades of life. To address these issues, functional magnetic resonance imaging (fMRI) was used to examine brain activation during spatial working memory retrieval in 45 healthy individuals between 20 and 68 years of age. Participants performed a modified version of the Corsi Block-Tapping test (CBT). The CBT requires the storage and subsequent reproduction of spatial target sequences and allows modulating working memory load by a variation of sequence length. Results revealed that activation intensity at the lowest CBT load level increased with increasing age and positively correlated with the number of errors. At higher CBT load levels, activation intensity decreased with increasing age together with a disproportional accuracy decline on the behavioral level. Moreover, results suggests that younger individuals showed higher activation intensity at high CBT load than at low CBT load switching to the opposite pattern at an age of about 40 years. Consistent with the assumptions of the Compensation-Related Utilization of Neural Circuits Hypothesis (CRUNCH), the present results reveal specific age-related alterations in left dorsolateral prefrontal cortex activation in response to increasing task load. Specifically, the results point towards increasing neural inefficiency with age at low task load and a progressive limitation of resources with age at higher task load. The present findings argue for an increasing functional cerebral dysfunction over a time span of 50 years that may partly be compensated on the behavioral level until a resource ceiling is approached.